(untitled) (Huellas, 2024)
The aim of this work is to examine the unequal production and marketing structures in the Argentine yerba mate circuit through the analysis of different organizations devoted to the transformation of this raw material in the province of Misiones. To achieve this objective, the study will focus on a comparative analysis of two drying facilities: one is a cooperative and the other is part of one of the leading Argentine companies in yerba mate production and marketing. The research proposal is organized on the basis of three analysis dimensions: size and organizational structure, access to resources, and labor relations. The data collection techniques employed include fieldwork in both entities, with the application of participant observation and multiple semi-structured interviews.